Utilization of Immobilized Rhizopus oryzae Lipase for Enzymatic Interesterification of Sesame Oil and Palm Stearin - Windiarti, Linda; Pudji Hastuti; Tyas Utami (Department of Food Science and Biotechnology, Faculty of Agroindustrial and Biosystem Technology, Universitas Brawijaya, 2026)
This study aimed to evaluate the activity of immobilized Rhizopus oryzae lipase (ROL) and its application in enzymatic interesterification (EIE) of sesame oil (SO) and palm stearin (PS) for margarine fat production. ROL was immobilized using immunobeads and tested for hydrolysis and esterification activities at 40–60 °C. Peak activity for both reactions occurred at 50 °C (92.5 U/g and 1818.3 U/g, respectively). Reusability tests showed declining activity over three cycles. EIE was performed at 50 °C for 24–48 h using SO:PS ratios of 60:40 and 50:50 (w/w). Slip melting point (SMP) and melting point (MP) were measured and analyzed statistically. The 50:50 ratio with 9-12 hours duration of EIE yielded a MP close to human body temperature (36–37 °C). The findings highlight ROL’s effectiveness as a reusable biocatalyst for producing margarine fat with desirable melting characteristics.